Ethnic disparities in risk of cardiovascular disease, end‐stage renal disease and all‐cause mortality: a prospective study among Asian people with Type 2 diabetes. Issue 3 (8th December 2015) - Liu, J. J.; Lim, S. C.; Yeoh, L. Y.; Su, C.; Tai, B. C.; Low, S.; Fun, S.; Tavintharan, S.; Chia, K. S.; Tai, E. S.; Sum, C. F.
Abstract: Aim: To study prospectively the ethnic‐specific risks of cardiovascular disease, end‐stage renal disease and all‐cause mortality in patients with Type 2 diabetes mellitus among native Asian subpopulations. Methods: A total of 2337 subjects with Type 2 diabetes (70% Chinese, 17% Malay and 13% Asian Indian) were followed for a median of 4.0 years. Time‐to‐event analysis was used to study the association of ethnicity with adverse outcomes. Results: Age‐ and gender‐adjusted hazard ratios for cardiovascular disease in ethnic Malay and Asian Indian subjects were 2.01 (1.40–2.88; P <0.0001) and 1.60 (1.07–2.41; P =0.022) as compared with Chinese subjects. Adjustment for conventional cardiovascular disease risk factors, including HbA1c, blood pressure and lipid profile, slightly attenuated the hazards in Malay (1.82, 1.23–2.71; P =0.003) and Asian Indian subjects (1.47, 0.95–2.30; P =0.086); However, further adjustment for baseline renal function (estimated GFR) and albuminuria weakened the cardiovascular disease risks in Malay (1.48, 0.98–2.26; P =0.065) but strengthened that in Asian Indian subjects (1.81, 1.14–2.87; P =0.012). Competing‐risk regression showed that the age‐ and gender‐adjusted sub‐distribution hazard ratio for end‐stage renal disease was 1.87 (1.27–2.73; P =0.001) in Malay and 0.39 (0.18–0.83; P =0.015) in Asian Indian subjects. Notably, the difference in end‐stage renal disease risk among the three ethnic groups was abolished after further adjustment for baseline estimated GFR and albuminuria. There was no significant difference in risk of all‐cause mortality among the three ethnic groups. Conclusions: Risks of cardiovascular and end‐stage renal diseases in native Asian subjects with Type 2 diabetes vary substantially among different ethnic groups. Differences in prevalence of diabetic kidney disease may partially explain the ethnic disparities. What's new?: This is the first prospective study to examine ethnic disparities in cardiovascular disease, end‐stage renal disease and all‐cause mortality risks among native South‐East Asian people with Type 2 diabetes. Ethnic Malay and Asian Indian subjects had a higher risk of cardiovascular disease as compared with Chinese subjects. The risk of end‐stage renal disease was significantly higher in Malay subjects, whereas it trended lower in Asian Indian as compared with Chinese subjects. The disparity in cardiovascular disease and end‐stage renal disease risks among ethnic subpopulations might be partially explained by difference in the prevalence of diabetic kidney disease. Our data highlight the importance of primary prevention of diabetic kidney disease in Asian people with Type 2 diabetes.